Effects of silane application on the shear bond strength of ceramic orthodontic brackets to enamel surface - Pinandi Sri Pudyani; Setiarini Widiarsanti (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2016)
Background: Fixed orthodontic appliances with ceramic brackets are used frequently to fulfill the aesthetic demand of patient through orthodontic treatment. Ceramic brackets have some weaknesses such as bond strength and enamel surface damage. In high bond strength the risk of damage in enamel surfaces increases after debonding. Purpose: This study aimed to determine the effect of silane on base of bracket and adhesive to shear bond strength and enamel structure of ceramic bracket. Method: Sixteen extracted upper premolars were randomly divided into four groups based on silane or no silane on the bracket base and on the adhesive surface. Design of the base on ceramic bracket in this research was microcrystalline to manage the influence of mechanical interlocking. Samples were tested in shear mode on a universal testing machine after attachment. Following it, adhesive remnant index (ARI) scores were used to assess bond failure site. Statistical analysis was performed using a two-way Anova and the Mann-Whitney test. A scanning electron microscope (SEM) with a magnification of 2000x was used to observe enamel structure after debonding. Result: Shear bond strength was increased between group without silane and group with silane on the base of bracket (p<0,05). There was no significance different between group without silane and group with silane on adhesive (p<0,05). Conclusion: Application of silane on base of bracket increases shear bond strength, however, application of silane on adhesive site does not increase shear bond strength of ceramic bracket. Most bonding failure occurred at the enamel adhesive interface and damage occurred on enamel structure in group contains silane of ceramic bracket.